Physics in traditions: the ritual of the owners of the Mexican sky. (August 2019) - Espíndola., R.; Del Valle, G.; Hernández, G.; Muciño, D.; Guijosa, S.; Jiménez, J. L.; Campos, I.
Abstract: Mexico is characterized by its immense cultural diversity, one culture of many is in the state of Veracruz where the Totonac culture lived. His developed of a ritual known as "The Papantla flyers"[1], which is related to fertility of the earth, this ritual consists of a group of five men who climb to the top of a 31-meter pole, tie a rope around their waist and throw themselves headlong into the void with open arms. A child, observing this ritual asks his father, "at the top, the pole has an engine that unrolls the rope and causes men to descend?". In this work, we study the equations of motion associated to the trajectory of the men who are thrown into the void, through the design and construction of an experimental model. To compare the experimental results with the analytical solution obtained by proposing the analytical equation that describes its movement, at the same time emphasizing the use of computational tools for simulation of the model using Easy Java Simulation.